2013
DOI: 10.1074/jbc.m113.452623
|View full text |Cite
|
Sign up to set email alerts
|

The Tryptophan Residue at the Active Site Tunnel Entrance of Trichoderma reesei Cellobiohydrolase Cel7A Is Important for Initiation of Degradation of Crystalline Cellulose

Abstract: Background: Mutation of Trp-40 in the Cel7A cellobiohydrolase from Trichoderma reesei (TrCel7A) causes a loss of crystalline cellulose-degrading ability. Results: Mutant W40A showed reduced specific activity for crystalline cellulose and diffused the cellulose chain from the entrance of the active site tunnel. Conclusion: Trp-40 is essential for chain end loading to initiate processive hydrolysis of TrCel7A. Significance: The mechanisms of crystalline polysaccharide degradation are clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
76
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 36 publications
8
76
0
Order By: Relevance
“…40 In addition, because PASC contains large numbers of cellulose chain ends and free chains for the initiation of endotype hydrolysis, 32 capturing the substrate chain by CD or decrystallization of the substrate is not a rate-limiting step. 41 In the hydrolysis of crystalline cellulose I α , the relationship among the three enzymes was similar to that of processivity whereas the difference between PcCel7D and TrCel7A was smaller in cellulose III I hydrolysis. The big difference between the two crystalline celluloses is the shape of the crystal.…”
Section: ■ Discussionmentioning
confidence: 88%
“…40 In addition, because PASC contains large numbers of cellulose chain ends and free chains for the initiation of endotype hydrolysis, 32 capturing the substrate chain by CD or decrystallization of the substrate is not a rate-limiting step. 41 In the hydrolysis of crystalline cellulose I α , the relationship among the three enzymes was similar to that of processivity whereas the difference between PcCel7D and TrCel7A was smaller in cellulose III I hydrolysis. The big difference between the two crystalline celluloses is the shape of the crystal.…”
Section: ■ Discussionmentioning
confidence: 88%
“…One suggested role of Trp is that "stacking" interactions of -electrons in its aromatic ring and the ␣-face of the carbohydrate (50) enable the necessary sliding of the bound chain (4, 51), possibly through stabilization of the transition state between adjacent positions in the processive movement (52,53). Tryptophan residues near the entrance of the active tunnel are also important for the initial "threading" and recognition of the cellulose strand, particularly on crystalline substrates (16,26,38,44,54). In the current work, we used the W38A mutation in T. reesei Cel7A to obtain an enzyme with weakened substrate affinity.…”
Section: Discussionmentioning
confidence: 99%
“…Many mutational studies in which Trp has been replaced with nonaromatic residues have shown negative effects on activity and processivity of, for example, cellulases (16,36,38,(43)(44)(45)(46) and chitinases (47)(48)(49). One suggested role of Trp is that "stacking" interactions of -electrons in its aromatic ring and the ␣-face of the carbohydrate (50) enable the necessary sliding of the bound chain (4, 51), possibly through stabilization of the transition state between adjacent positions in the processive movement (52,53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GH7s contain a conserved tryptophan residue, Trp40 in TrCel7A, which binds to the glucopyranose ring at the −7 site in GH7 structures (31). This tunnel entrance tryptophan residue has been implicated in cellulose chain complexation (36,37), and its stacking interaction with the glucopyranose ring at the −7 site remains intact during the simulation. These results suggest that the Trp40 residue is responsible for acting as a large, hydrophobic platform for chain binding when the enzyme is bound to a cellulose crystal, and that this binding site delineates the decrystallized chain from the cellulose crystal.…”
Section: Simulations Predictmentioning
confidence: 99%